2020
DOI: 10.3389/fphar.2020.00538
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine and Gut Microbiome: Their Respective and Concert Effects on Healthcare

Abstract: Advances in systems biology, particularly based on the omics approaches, have resulted in a paradigm shift in both traditional Chinese medicine (TCM) and the gut microbiome research. In line with this paradigm shift, the importance of TCM and gut microbiome in healthcare, as well as their interplay, has become clearer. Firstly, we briefly summarize the current status of three topics in this review: microbiome, TCM, and relationship of TCM and microbiome. Second, we focused on TCM's therapeutic effects and gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 144 publications
0
41
0
Order By: Relevance
“…In an attempt to investigate the mechanisms underlying the beneficial effects of this extract combination, the analysis of the gut microbiome has gained our attention, since: i. a large number of recent studies have showed that herbal medicines are capable of reversing the abnormal gut microbiota composition in diseased human cohorts and model animals [ 58 , 59 ], and ii. gut-microbiota derived metabolites are capable to regulate miRNA expression with effects on metabolism [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to investigate the mechanisms underlying the beneficial effects of this extract combination, the analysis of the gut microbiome has gained our attention, since: i. a large number of recent studies have showed that herbal medicines are capable of reversing the abnormal gut microbiota composition in diseased human cohorts and model animals [ 58 , 59 ], and ii. gut-microbiota derived metabolites are capable to regulate miRNA expression with effects on metabolism [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that TCM could interfere with GM [ 184 ]. Changes in composition and diversity using TCM could be achieved by interference with gastrointestinal pH and transit time, as well as by affecting GM enzymes and metabolites [ 185 ]. In addition, some TCM compounds (such as Xiexin Tang and other herbs) can reshape the GM in T2DM rats, viewed by increased abundance of bacteria with the ability to synthesize SCFAs and with anti-inflammatory properties [ 186 ].…”
Section: Therapeutic Opportunities For Covid-19 With Impact On Thementioning
confidence: 99%
“…Different TCM formulae contain an array of small chemical molecules with a number biological functions, including flavonoids, saponins, alkaloids, and anthraquinones, etc. (Xu et al, 2013;Yan et al, 2013;Chen et al, 2015;Zhang et al, 2020b) (Table 1). Both gut microbiota and the liver involve conversion of the xenobiotics ingredients into subsequent metabolites (Fig.…”
Section: Transformation Of Tcm Small Chemical Molecules By Gut Microbmentioning
confidence: 99%